Kajian Penerapan dan Hasil Kebijakan Agropolitan di Kabupaten Lima Puluh Kota - Hari, Kimiawan; Muktialie, Mohammad (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
The implementation of the Indonesian Ministry of Agricultureâ€™s Agropolitan Policy bares varying results in each area. The outcome of such federal policy, is determined by 1) the structure of the implementation, 2) policy instrument, 3) community participation, and 4) the availability of resources. Lima Puluh Kota Regency in West Sumatra is one of the regions implementing this policy, starting in Mungka District as an Agropolitan District in 2005. The implementation expected an increase in the communityâ€™s revenue and productivity by 5%. Analysis showed that in early 2012, the 5% income rise only happens to 63.04% of the population, while 5% increase in productivity only occurs to 34.78%. Further analysis showed that the low outcome is a result of: 1) lack of clarity in the guidelines issued by the Ministry, 2) lack of legal basis for enforcement of the Agropolitan Master Plan, 3) inconsistencies in the agropolitan working group in Lima Puluh Kota Regency, 4) inefficiency of the organizational structure (Susunan Organisasi dan Tata Kerja â€ SOTK) of Lima Puluh Kota Regency , 5) lack of knowledge and number of counselors in BP3K Mungka to assist the community, 6) lack of support from the local budget committee in the allocation of funding, 7) lack of involvement from the Pemerintah Nagari in implementation of the program, and 8) lack of coordination and communication between the executives and legislatives.